Evaluation of a stone consolidant for preserving white marble in cultural heritage conservation - Yukuan Wang; Hongli Liu; Yameng Liu (AIP Advances)
This paper evaluates using a newly formulated consolidant, JSY-01, for stone in restoring cultural heritage artifacts, white marbles. White marble is susceptible to environmental degradation, and sealing alone may not be effective unless it drastically changes its color. Marble samples from different regions with varied chemical compositions, based on their hydrophobicity, breathability, ultraviolet (UV) aging resistance, and chemical durability, were tested with JSY-01. The test results show that JSY-01 enhances water resistance, significantly reduces water absorption, and maintains breathability to prevent the damaging effects of moisture. The material was also shown to resist UV irradiation with minimum color changes and improved marble surface hardness and gloss without compromising the aesthetic integrity. In addition, resistance to acidic and saline environments further established suitability for outdoor applications. This has general utility across marble types, which suggests that there is a broad scope of applicability. Hence, the solution is practical for heritage conservation. The study concludes that JSY-01 is a long-term reversible consolidant and adheres to conservation ethics. These results advance sustainability in practices of conserving cultural heritage, thus scientifically validating solutions for preserving durability and aesthetics in marble artifacts exposed to environmental stresses.